(untitled) (Journal of the College of Basic Education, 2025)
This study talks about the estimated difference in morphological structures in which the verbal image is the same and the meaning is different, and this includes the structures of nouns and verbs, because knowing the difference between the structures is of great importance in understanding the meaning given by this or that structure, and this is done by understanding the verbal difference between them, as the two structures are similar in pronunciation and the difference between them remains estimated, and this can be known by referring to the origin of the word’s structure and weight, and this matter is not surprising in Arabic and has evidence and examples, and the context is what clarifies that.